Optoelectronic measurement of wrist movements in various casts and orthoses used in scaphoid fractures. (July 2019) - Waton, Andrew; Forrest, Sarah; Whatling, Gemma M.
We developed an optoelectronic motion analysis protocol to measure anatomical and functional ranges of wrist motion in Colles'-type and scaphoid-type splints and casts. The protocol was used to study the restriction of wrist motion in casts and splints in ten healthy volunteers. Scaphoid-type casts were no more restrictive to wrist motion than Colles'-type casts, but casts were significantly more restrictive than removable splints. Removable splints were more restrictive than no immobilization. Results suggest there is no benefit in using scaphoid-type casts rather than Colles'-type casts to reduce wrist motion.